ANALISA PERBANDINGAN RESPONSE TIME DAN THROUGHPUT PADA XML DAN DBMS SEBAGAI MEDIA PENYIMPANAN DATA - Ragil Martha; Yanuar Firdaus; Kusuma Ayu Laksitowening (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2010)
In the environment where information exchanges running rapidly, performance becomes a matter that isabsolutely necessary to ensure the accuracy and speed of information delivery. Response time and throughputare two of the performance parameters that could be considered in choosing data storage media. A DBMS is aset of software programs that controls the organization, storage, management, and retrieval of data in adatabase. Along with the development of information technology, the needs of DBMS as storage media would becrucial. In addition to DBMS, there is another data storage format -had a similar structure to that relational-named XML. Nowadays Native XML Databases had been introduced as a new technology of XML. In NativeXML Databases, XML files could be related one to another just like in DBMS. The objective of the research wasto analyze what is best between those two data storage format. The analysis result concluded that DBMS givelower response time and greater throughput.Keywords: Native XML Database, XML, DBMS, response time, throughput